Reimajinasi Mahabbah dalam Islam: Perspektif Komparatif atas Pemikiran Al-Ghazali dan Jalaluddin Rumi - Zakiyah; Saepudin (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study explores the comparative construction of mahabbah in the thought of al-Ghazali and Jalaluddin Rumi. Using a qualitative approach with comparative and content analysis, it examines primary sources such as Ihya' Ulum al-Din, Kimiya' al-Sa'adah, Fihi Ma Fihi, and the Mathnawi, along with relevant secondary literature. The findings indicate that al-Ghazali views mahabbah as the culmination of spiritual ascent, reached progressively through the maqamat. For him, love is the highest station, the fruit of ma'rifah, expressed in obedience and inner contentment. By contrast, Rumi presents love as the sole path to healing spiritual maladies, a transformative journey toward God through gnosis and mystical union. The study highlights how ethical and mystical orientations to divine love offer distinct yet complementary perspectives, enriching the broader discourse on Sufi spirituality.